Metal Cutting. - Trent, E. M. (Edward Moor) (Butterworth Heinneman, 1991)
Analyzing the processes of metal cutting and tool wear and discussing the machinability of work materials, this book is designed as a practical reference for those engaged in machining, tool-making and related engineering activities as well as students of metallurgy and engineering.
Keywords: Metal-cutting.; Metal-cutting tools